Classroom Management Strategies to Increase Students' Interest in Learning in Elementary Schools - Uni Nurnikmah; Primanita Sholihah Rosmana; Sofyan Iskandar; Ica Nurlaela (al-Afkar, Journal For Islamic Studies, 2025)
This research is a qualitative description with data collection methods such as interviews, observations, and literature studies regarding classroom management to increase students' interest in learning. The aim is to describe the supporting factors, strategies, obstacles, and effectiveness of classroom management to increase elementary school students' interest in learning. The data used is secondary data. The research results show that classroom management does not only focus on technical or strategic aspects, but also pays attention to the individual characteristics of the students who attend the class. Therefore, it is important for teachers to continue to improve their skills in classroom management to ensure that an optimal learning environment can be created, thereby fostering students' interest in learning and facilitating better academic achievement